2016
DOI: 10.1530/joe-15-0435
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E1 inhibits endocytosis in the β-cell endocytosis

Abstract: Prostaglandins inhibit insulin secretion in a manner similar to that of norepinephrine (NE) and somatostatin. As NE inhibits endocytosis as well as exocytosis, we have now examined the modulation of endocytosis by prostaglandin E 1 (PGE 1 ). Endocytosis following exocytosis was recorded by whole-cell patch clamp capacitance measurements in INS-832/13 cells. Prolonged depolarizing pulses producing a high level of Ca 2+ influx were used to stimulate maximal exocytosis and to deplete the readily releasable pool (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Standard whole‐cell patch‐clamp recordings were performed as previously described (Zhao et al ) to measure capacitance changes and Ca 2+ currents and determine readily release pool (RRP) size. Patch pipettes were pulled to have resistances of around 3 MΩ with intracellular solutions.…”
Section: Methodsmentioning
confidence: 99%
“…Standard whole‐cell patch‐clamp recordings were performed as previously described (Zhao et al ) to measure capacitance changes and Ca 2+ currents and determine readily release pool (RRP) size. Patch pipettes were pulled to have resistances of around 3 MΩ with intracellular solutions.…”
Section: Methodsmentioning
confidence: 99%
“…These metabolites subsequently regulate various cellular functions in autocrine and/or paracrine fashions. It has been shown that endogenous PUFA metabolites, such as 20-hydroperoxyeicosatetraenoic acid (20-HETE), prostaglandin E1, E3, J2 and I2, or endocannabinoids regulate beta cell functions [14,16,29,30,31,32,33,34,35,36,37,38,39]. Some of these mediators are also generated in beta cells by direct enzymatic transformation of exogenously available unsaturated fatty acids; it has been shown that certain metabolites improved insulin secretion and ameliorate obesity- and cytokine-induced beta cell damage [16,40,41].…”
Section: Phospholipid Turnover In Cellsmentioning
confidence: 99%